Integrating Geospatial Technology in Learning: An Innovation to Improve Understanding of Geography Concepts - Manakane, Susan E; Latue, Philia Christi; Rakuasa, Heinrich (Sinergi International Journal of Education, 2023)
This research discusses the integration of geospatial technology in geography learning as an innovation to improve students' understanding of geography concepts. This research uses literature study method to investigate the importance of geospatial technology integration in geography learning with the aim of improving students' understanding of geography concepts. The results show improvements in visualization of abstract concepts, introduction of global and local concepts, development of analytical skills, and more active student interaction. Constraints such as facility availability and teacher training were also recognized. The integration of geospatial technology opens up opportunities for more engaging and effective contextualized learning in the digital era.